The ATM gene and susceptibility to childhood T-cell acute lymphoblastic leukaemia - Takeuchi, Seisho; Koike, Michiaki; Park, Susan; Seriu, Taku; Bartram, Claus R.; Taub, Harry E.; Williamson, Ian K.; Grewal, Jeffrey; Taguchi, Hirokuni; Koeffler, H. Phillip (British journal of haematology, 1998)
Ataxia-telangiectasia (A-T) is a multisystem recessive disease characterized by cerebellar ataxia, oculocutaneous telangiectasias, immunodeficiency and increased risk of cancer. The ATM gene, responsible for A-T, was recently cloned at human chromosome band 11q22-23, a region of frequent alterations in childhood acute lymphoblastic leukaemia (ALL). Children with A-T frequently develop T-ALL. We investigated 18 T-ALL samples for ATM mutations and loss of heterozygosity (LOH) at the ATM locus. No mutations of ATM were found within the coding region in the 18 T-ALL samples, and LOH at the ATM locus was detected in three. The ATM gene appears to be an infrequently altered tumour suppressor gene in childhood T-ALL.